Rethinking the practice of accountability journalism in the digital age. The inception and development of the first Portuguese university-based investigative journalism centre and whistleblowing platform - Giachi, Francesca (2018)
At a time of worrying change, when Western traditional media outlets appear to be engulfed by the collapse of the advertising-based business model and can hardly bear the strain brought about by new technologies, the present study identifies an increasing information deficit as regards quality accountability reporting. Taking up Duffield and Cokley’s challenge to change in response to the demands of the time, the present paper supports the development of VALQUIRIA, at https://valquiria.org, a transmedia, multiplatform investigative journalism project integrated in the Faculty for Humanities and Social Sciences of the NOVA University of Lisbon. Valquíria, adopting a new sustainable media model, represents the very first attempt in Portugal to create a completely independent space for the education of investigative journalists, the assistance to foreign and local reporters, the production and diffusion of accountability reporting, technological products and innovative practices which can aid the profession. Featuring a vibrant crowd-sourcing and collaborative policy, its ultimate aim is to reinvigorate and enhance the practice of accountability journalism in Portugal, proving its urgency for preserving and guarding a healthy democracy. To change even more the traditional paradigm of public interest journalism, the project features a whistleblowing platform called PTLeaks: built in cooperation with the HERMES Center for Transparency and Digital Human rights, it is the first Portuguese GlobaLeaks initiative applied to investigative journalism.